Pengembangan Media Video Pembelajaran Pada Mata Kuliah Fotografi - Rifky Aditya; Zuliarni Zuliarni (Journal of Pedagogy and Online Learning, 2022)
This study aims to produce video media products using Wondershare Filmora as a learning medium that is in accordance with the eligibility criteria for media and materials in photography courses. The research conducted is Research and Development (R&D) research. The product validity test was carried out by three validators, namely two media validators and one material validator. The product trial was carried out for students of the 2020 FIP UNP ID card affairs who were the subject of trials with a total of 20 people to find the feasibility of learning video media. Data collection instruments and tools used are documentation, material and media expert validation formats, assessment sheets and questionnaires. Based on the results of the feasibility assessment from material experts and media experts, namely, the results of material validation obtained a "Very good" value so that the material was declared valid for use, the media validation results obtained a "Very Good" value, so the media was categorized as valid for testing. Furthermore, the results of the analysis based on trials for the practicality of learning video media products are in the "Very Practical" category. Based on the results of the validity test, and the trial, it can be concluded that learning video media can be developed and effectively used in the Photography learning process.